Femininas, porém masculinas : controvérsias de gênero no universo das policiais militares de Minas Gerais - Natália Ávila de Castro (2016)
This paper aims to investigate, through research with so-called "female police officers" of the Military Police of Minas Gerais, the different perspectives of these women on controversial gender issues in the military police universe. The methodology, multi sited, had semi-structured interviews with twelve women, reports analysis and ethnographic observations. Without claiming to reach fixed and permanent conclusions, I analyze disputes and tensions around the three pairs of opposition equality-difference, nature-culture and male-female, constantly evoked in anthropological debates about gender. For this, I base myself mainly on theories of Joan Scott, Donna Haraway, Marilyn Strathern and Bruno Latour, in order to contribute to the opening of the black boxes of these controversies on the experiences of the military police officers of Minas Gerais.